Chromium-Promoted Dearomative (Deutero)Hydrocyanoalkylation of (Hetero)Arenes Using Simple Alkylnitriles - Zeng, Wei-Long; Jiang, Xu; Li, Wei (Synlett, 2023)
Herein, a general strategy for the regioselective dearomative 1,2-hydrocyanoalkylation of chromium-bound (hetero)arenes with simple alkylnitriles as pronucleophiles was disclosed, providing rapid access to 1,3-cyclohexadienes possessing useful alkylnitrile groups. The versatility of this methodology further enabled a selective dearomative deuteration reaction. Finally, synthetic applications of the method in the formal synthesis of natural products, including erysotramidine, demethoxyerythratidinone, and morphine, were demonstrated.
Keywords: chromium; dearomatization; hydrocyanoalkylation; deuteration; alkylnitrile; cyclohexadiene